Strategy to Reduce Low Birthweight Babies in West Aceh Regency - Teungku Nih Farisni; Yarmaliza Yarmaliza; Fitrani Fitriani (Universitas Teuku Umar, 2019)
Low birthweight babies are babies with a birth weight of 1,500 grams to less than 2,500 grams. Low birthweight babies are the cause of increase in babies’ mortality (death) and morbidity (pain). One of the primary risk factors of low birthweight babies is poor pregnant mother’s nutrition. Iron can provide a reserve or storage of nutrition that is very much needed by pregnant mothers to prevent anemia and maintain optimal growth of fetuses. The occurrence of low birthweight babies in Aceh Barat Regency is still very high. The design of this research was observational with an intervention of providing iron for 90 days to pregnant mothers and nutritional guidance for pregnant mothers in the effort of reducing the prevalence of low birthweight babies. The research was done in 10 villages from 3 rural sub-districts that contribute to high rates of low birthweight babies in Aceh Barat Regency, with 146 pregnant mothers. The results of the research showed that the application of the informal guidance strategy in a non-formal setting accompanied with discussions among family members and guidance targets resulted in 69.2% of guidance targets becoming motivated to consume Fe tablets and maintain eating patterns, while guidance targets that have been motivated yet did not consume Fe tablets and maintain eating patterns gave low income of guidance and Fe tablets were observed for 3 months; the result was 13 mothers (86.7%) gave birth to babies of normal weight and 2 mothers (13,3%) gave birth to underweight babies. The application of the guidance strategy in the effort to reduce the occurrence of low birthweight babies, from the results of this research, requires commitment from the Department of Health to provide suitable funds, facilities, and infrastructure to provide services to pregnant mothers, and commitment of all health officials in particular village nurses and health cadres, as well as involving the husband in the role to maintain a healthy pregnancy.